The grammatical distinction between count nouns and mass nouns in Mandarin Chinese - Stoch, Nastazja (Lingua Posnaniensis, 2020)
The purpose of this paper is to prove the Mass Noun Hypothesis wrong. The hypothesis claims that all common nouns in classifier languages like Mandarin Chinese are mass nouns. The objection against it consists in displaying its implausible deduction, where false conclusions have been drawn due to relying on the grammar of English, which is incongruent with the grammar of Chinese. Consequently, this paper defends the Count Noun Thesis, stating that in Chinese there are count as well as mass nouns. In support of this statement, first, the typology of numeral classifiers had to be established, which resulted in gathering and completing all the reasons to distinguish classifiers from measure words. After only this necessary differentiation was made, it was possible to show that the count/mass distinction exists in Mandarin Chinese. That is, count nouns by default have only one classifier, with certain disclaimers. Apart from that, count nouns, as in every language, may undergo some measurement with measure words. Mass nouns, however, in the context of quantification may appear only with measure words, but not with classifiers. These conditions naturally follow from the ontological status of the two types of nouns’ referents, i.e. bounded objects denoted by count nouns, and scattered substances denoted by mass nouns.